The Effect of Supervision on Employee Performance With Work Commitment as a Variable Moderation at PT. Media Persada Technique - Zulpedri; Mesra B (Yayasan Multidimensi Kreatif, 2024)
Challenges in maintaining the effectiveness of the oversight system, lack of resources, and low levels of employee commitment underscore the importance of a holistic approach to improving organizational performance. The purpose of this study is to find out and analyze the influence of supervision on employee performance moderated by work commitment at PT. Media Teknik Persada. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 61 employees. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) show that 1) Supervision had no effect on employee performance with a T-statistic value of 0.816 < 1.96 and a P-Value of 0.418 > 0.05. 2) Work commitment has a positive and significant effect on employee performance with a T-statistic value of 3.169 > 1.96 and a P-Value of 0.002 < 0.05. 3) Moderating variables, namely work commitment, were not able to significantly strengthen the influence of supervision on employee performance with a T-Statistic value of 0.002 < 1.96 and a P-Value of 0.999 > 0.05. The implications of these findings explain that management must be able to take a more holistic approach to managing human resources, by focusing more on organizational culture through the involvement of work commitment, while considering effective and not excessive supervision in improving employee performance